2012
DOI: 10.5923/j.cmaterials.20120202.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Absorption on Color Stability of Different Resin Based Restorative Materials in Vitro Study

Abstract: This study was designed to evaluate the effect of water absorption of three resin based composite materials on their color stability Methods: using scanning spectrophotometer. A total of 45 disc samples were constructed from microhybrid resin composite, polyacid modified resin composite and giomer. It should be mentioned that the selected shade is A2. Then inserted in water for water absorption test. Using five different drink [mouth rinse (37•C) (Chlorohexidine containing mouthwash), tea, coffee, red wine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
(9 reference statements)
1
9
0
3
Order By: Relevance
“…In addition, compomers contain methacrylates which increase water absorption compared to the resin composite. The results of this study also showed that the wettability is better for the compomer than the resin composite 20) . McCabe and Rusby showed that the giomer has significantly greater water absorption than the compomer 21) .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In addition, compomers contain methacrylates which increase water absorption compared to the resin composite. The results of this study also showed that the wettability is better for the compomer than the resin composite 20) . McCabe and Rusby showed that the giomer has significantly greater water absorption than the compomer 21) .…”
Section: Discussionsupporting
confidence: 59%
“…The microhardness values of the restorative materials significantly decreased after 5 days of immersion in the experimental beverage groups compared to the initial value, and Coca-Cola most significantly affected the giomer microhardness. As the polymer material absorbs water, the coupling agent causes the loss of chemical bonds and hydrolysis occurs between the resin matrix and filler particles, affecting the microhardness 20) .…”
Section: Discussionmentioning
confidence: 99%
“…This situation causes plasticizer effect of the organic matrix and consequent degradation 17) . The degradation of the resin-filler interface and inorganic fillers may also play a role in the reduction of surface hardness 22) . The difference of hardness in the composite resins immersed in different beverages is also associated to the chemical composition 23) .…”
Section: Discussionmentioning
confidence: 99%
“…Os valores de SO foram semelhantes entre os grupos, e mais baixos que os valores máximos de SO recomendados, o que demonstra sua reduzida capacidade de absorver água e sofrer expansão volumétrica. Esta característica é desejável para os materiais, uma vez que a cavidade oral é um ambiente úmido e a absorção de água pelo compósito pode levar causar uma deterioração de suas propriedades 18,35,38 . Nos compósitos, a microdureza está relacionada ao grau de polimerização do material 39 .…”
Section: Resultsunclassified
“…A SO significa a capacidade deste material em absorver substâncias do meio, o que pode gerar alterações volumétricas do material 33,34 . Os efeitos destes dois fenômenos podem implicar em prejuízos à estrutura do polímero, influenciando a estabilidade de cor e a rugosidade do material 35,36 . Segundo a norma 4049 da ISO, as resinas compostas Pesquisa AVALIAÇÃO DO EFEITO DA TERMOCICLAGEM NA ESTABILIDADE DE COR E RUGOSIDADE SUPERFICIAL DE DUAS RESINAS COMPOSTAS COMERCIAIS Com a utilização de 2 mil ciclos de termociclagem, já foi possível observar uma influência na estabilidade de cor dos materiais avaliados, apesar dos valores terem ficado abaixo do limiar considerado perceptível clinicamente 26 .…”
Section: Discussionunclassified